Pengaruh Cash Ratio, Return on Equity, Debt to Equity Ratio, dan Ukuran Perusahaan terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Wibowo, Imam Tri; Andre, Fransicus Alex; Hakim, Astrid Dita Meirina; Kuncoro, Aris Wahyu (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to determine the effect of Casb Ratio, Return On Equity, Debt to Equity Ratio, and Company Size on Company Value in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange for the period 2018 – 2022. The sample for this study were 8 companies in the pharmaceutical sub-sector that were registered on the Indonesia Stock Exchange for the 2018-2022 period. This research was conducted using the panel data regression method assisted by the Eviews 10 program and Microsoft Excel 2016. The results showed that Cash Ratio, Return On Equity, and Firm Size partially had no significant effect on Firm Value. Meanwhile, the Debt to Equity Ratio has an effect on Firm Value.